2014
DOI: 10.1016/j.ejvs.2014.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Vascular Closure Using an Anchored Collagen Plug Provides Effective Haemostasis Following both Antegrade and Retrograde Femoral Arterial Punctures

Abstract: Angio-Seal deployment is successful for both antegrade/retrograde femoral punctures albeit with a higher antegrade failure rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…1 Due to its sealing features, we supposed FemoSeal could be equally effective in antegrade CFA puncture as it is in retrograde CFA puncture, as reported in literature for other VCDs in antegrade superficial femoral artery (SFA) and CFA puncture. 8,[14][15][16][17][18] The deployment technique and the artery involved are the same, and it only changes the deployment direction and the distance between the skin entrance and the arterial wall.…”
Section: Discussionmentioning
confidence: 99%
“…1 Due to its sealing features, we supposed FemoSeal could be equally effective in antegrade CFA puncture as it is in retrograde CFA puncture, as reported in literature for other VCDs in antegrade superficial femoral artery (SFA) and CFA puncture. 8,[14][15][16][17][18] The deployment technique and the artery involved are the same, and it only changes the deployment direction and the distance between the skin entrance and the arterial wall.…”
Section: Discussionmentioning
confidence: 99%
“…As per the instructions for use, there are no contraindications as such, especially relating to antegrade punctures. Angio-Seal deployment is reported to be successful for both antegrade and retrograde femoral punctures albeit with a higher antegrade failure rate [10]. Antegrade access is not contraindicated.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the largest prospective randomized trials of VCDs have been conducted with the Angio-Seal device. Kussmaul et al 1 showed a significant decrease in time to hemostasis following its use. In this trial, all complications, including bleeding were less common in the Angio-Seal arm than in the manual compression arm.…”
mentioning
confidence: 99%
“…Length of hospital stay has also been reported to be shorter with the Angio-Seal device. 1,2 Complication rates with the Angio-Seal device range from 0.8% to 3.6%. 1,3 The most commonly occurring complication with the use of the Angio-Seal device was arterial occlusion of the femoral artery at the puncture site caused by arterial narrowing and foreign body reaction caused by the intra-arterial anchor.…”
mentioning
confidence: 99%
See 1 more Smart Citation